Simple boost converter using timer IC 555 for charging capacitor banks - Mohamed, Mohd Rezal; Mariun, Norman; Aris, Ishak (IEEE, 2010)
A boost converter is capable to increase input voltage to a certain voltage level which is required by a high voltage load. In this project, a 12V battery is used as input voltage to the boost converter circuit. The Timer IC 555 is the main control device used to control the switching of the MOSFET. The main objectives of this project are to study and design a simple, portable, and low cost boost converter for charging capacitor banks.